2019
DOI: 10.1007/s12687-019-00435-6
|View full text |Cite|
|
Sign up to set email alerts
|

Perspectives of adults with Klinefelter syndrome, unaffected adolescent males, and parents of affected children toward diagnosis disclosure: a Thai experience

Abstract: Little is known about disclosure of diagnosis to males with Klinefelter syndrome (KS) diagnosed before birth or during childhood, especially in Asian context. Insufficient preparation for disclosure communication could lead to the child's depression, anxiety, or disrupted self-esteem. This is an interventional and qualitative interview study with a brief self-reported survey. The study consists of three phases. In phase I, adults with KS were asked about their experiences and viewpoints toward KS disclosure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…We observed that the mean age of patients with KS was 25 years. KS has been reported to be severely underdiagnosed or diagnosed late in life, usually on workup for infertility; roughly 25% are diagnosed, and the mean age of diagnosis is in the mid-30s [ 19 ]. Bojesen also found that 65% to 85% of KS patients consulted doctors after the age of 25 years for overt hypogonadism signs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the mean age of patients with KS was 25 years. KS has been reported to be severely underdiagnosed or diagnosed late in life, usually on workup for infertility; roughly 25% are diagnosed, and the mean age of diagnosis is in the mid-30s [ 19 ]. Bojesen also found that 65% to 85% of KS patients consulted doctors after the age of 25 years for overt hypogonadism signs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when a chromosomal aneuploidy is diagnosed during prenatal age/childhood, parents often face the decision of "how and when" to disclose the diagnosis to their child. Few data are currently available in the literature on this issue and more evidence is needed to establish best practices (Suwannachat et al 2020;Tremblay et al 2016). Understanding at which age communication should occur would be useful since it may influence diagnosis acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding at which age communication should occur would be useful since it may influence diagnosis acceptance. In the view of unaffected adolescent males, late disclosure may involve such disadvantages as greater difficulty in diagnosis acceptance (Suwannachat et al 2020 ). Previous evidence reports that age of diagnosis communication negatively correlates with adaptation, suggesting that older participants experience more challenges throughout their lives compared to younger subjects (Turriff et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations